THE CHEMICAL CHARACTERISTICS AND ANTIOXIDANT ACTIVITY OF STARCH FROM SAGO BARUK PITH (Arenga microcarpha) - Lidya Irma Momuat; Edi Suryanto; Sri Sudewi (Molekul, 2016)
Sago Baruk (Arenga microcarpha) is one of endemic crop type of Archipelago of Sangihe Talaud, North Sulawesi and potential as source bioactivities including antioxidant. The objectives of this research were to determine the chemical characteristics and antioxidant activity of starch sago baruk which was sequentially extracted with water and filtrate. The sago trunks pith was sequentially extracted with water and filtrate at room temparature for 1 hour. After that, starch of sago baruk were analyzed for their chemical composition (moisture, fat, protein, ash crude fiber and charbohydrate) and total phenolic and tannin condensed content. Antioxidant activity of each sago flour were evaluated in 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging and total antioxidant capacity. After that, the starch was characterized by IR spectroscopic technique. The sequential extraction result indicated percentage yield of starch I and starch II were 41.39% and 38.21%. The chemical characteristics of starch I revealed that percentage protein, ash, crude fibre and fat were below 1% than starch II especially protein and fiber crude. The starch I had highest total phenolic and tannin condensed content than starch II and starch K. The starch I also showed the highest free radical scavenging activity in 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical than starch II and starch K. The result also showed that starch I has strongest total antioxidant capacity than starch II and starch K at all concentration level. Antioxidant activity of three starch increased with the increase in concentration of the samples. The three starch showed of hidroxy (OH), carbonyl (C=O), ether (C-O) and aliphatic group (C-C). It is concluded that starch sago baruk especially the starch I are very rich in antioxidant substituens.